STRATEGI KOMUNIKASI PEMASARAN DALAM UPAYA MENINGKATKAN PENJUALAN PADA INSTAGRAM MATERNAL DISASTER - Amalia Crismoni, (2021)
In today's very rapid technological developments, business people use social media to dominate market pairs. Currently, Instagram is the most popular social media for most people, supported by increasingly sophisticated mobile phones as well as internet networks that are easily available, therefore Maternal Disaster uses Instagram as a tool for promotion. The marketing communication strategy was made by maternal disaster with the aim of knowing the marketing communication strategy in an effort to increase sales on maternal disaster instagram. The type of this research is descriptive qualitative. After conducting the analysis, the conclusion of this research is that maternal disaster uses a promotional mix of advertising, personal selling, sales promotion and public relations by using social media Instagram as a place to share information about its products, carry out activities promotions such as membership, discounts and free gifts.